(untitled) (The Review of Diabetic Studies, 2025)
Background: Magnetic Resonance Imaging (MRI) is a cornerstone non-invasive modality for the early detection and ongoing monitoring of neurodegenerative diseases. Given its capacity to provide detailed insights into cerebral structural and functional alterations, MRI is a highly sensitive component within multimodal diagnostic frameworks. Objectives: This study was designed to investigate the diagnostic efficacy of MRI for the early identification of neurodegenerative diseases and to elucidate its potential clinical applications. Methods: We conducted a cross-sectional study involving a cohort of 114 participants. The final sample consisted of 57 patients with early-stage neurodegenerative disease and 57 healthy controls. The patient subgroup was comprised of 24 individuals with early-stage Parkinson’s disease (42.1%) and 33 with early-stage Alzheimer’s disease (57.9%). MRI-based quantitative analysis was employed to identify and compare structural and functional metrics between the two cohorts. Results: The patient group demonstrated a 13.9% reduction in hippocampal volume compared to the controls (p<0.05). Additionally, the mean cortical thickness of the medial temporal lobe was significantly lower in patients (2.33±0.18 mm) than in controls ( 2.49±0.15 mm, p<0.05). The prevalence of moderate-to-severe white matter hyperintensities was markedly higher in the patient cohort (47.4%) compared to the controls (14%). These metrics exhibited robust discriminative capacity, with the analysis yielding an optimal diagnostic threshold that demonstrated a sensitivity of 89.5% and a specificity of 85.9%. Conclusion: This research corroborates the existence of significant neuroanatomical and microstructural distinctions between individuals with early-stage neurodegenerative disease and healthy controls. These findings emphasize the clinical utility of MRI as a sensitive and robust method for the early diagnosis of neurodegenerative diseases.